Creating Discursive Space for Intercultural Encounters: La Casa Encendida, Madrid. (January 2015) - Moore, Michelle
Abstract As increasingly heterogeneous museum audiences seek to participate actively in museum discourses, a new question arises: who is included in the conversation? This article extends that question to cultural‐spatial production, and seeks to illuminate key players' roles in creating spaces that welcome marginalized groups in order to facilitate intercultural encounters. It argues that inclusive, discursive environments are as much a product of "scripting as design." La Casa Encendida (The Incandescent House), a cultural center in Madrid, Spain, is used as a case study. It is examined in two stages: first, the ambitions and strategies of its makers and managers are explored; second, project outcomes are tested following the staging of Mundo Extreme (Extreme World), an exhibition that aimed to mediate between the hidden cultural worlds of artists with intellectual disabilities and wider arts scenes. This analysis highlights the contribution of cultural‐spatial production and occupation strategies to facilitating, revealing, and drawing into dialogue marginalized groups.